'Labour', A Brief History of a Modern Concept. (17th April 2022) - Honneth, Axel
Abstract : As has often been observed, neither the thinkers of antiquity nor those of the Middle Ages exhibited a great theoretical interest in the social value or even the ethical significance of labour. Throughout this long period of history, the labour an individual had to carry out to make a living, and thus under compulsion, was understood more or less solely as a heavy burden. It signified daily toil and the state of personal dependency attaching to a lowly social rank. Consequently, there was no cause to subject it to any kind of moral consideration. Indeed, as Moses Finley reports (1999, p. 81) '[n]either in Greek nor Latin was there a word with which to express the general notion of 'labour' or the concept of labour as a general social function' (see too Arendt, 2013 [1958], pp. 81 ff.). Famously, with the advent of modernity, the very opposite begins to become the case. In this period, in the wake of various intersecting processes of cultural revaluation and economic transformation, labour developed into a positive credential of free existence and a presupposition of social integrity: the Protestant ethic led to a gradual upgrading of the value of labour, because it was interpreted as a sign that one possessed a capacity for inner-worldly asceticism. In the course of the establishment of capitalist economic practices, the liberation of labour from personal dependency in legal terms gave rise to the idea that gainful work could henceforth be proof of a free decision, and it thus provided the precondition of individual independence. And over time, the more the intellectual union between these two revolutions was strengthened, the more it would go on to influence the cultural self-understanding of modern societies in the capitalist west: what was previously the sheer necessity of earning a daily crust was now understood as proof of social emancipation and freedom. Nobody provided a better conceptualisation of this transformed self-conception than Georg Wilhelm Friedrich Hegel, who devoted an entire chapter of his 'Philosophy of Right' of 1821 to the emancipatory value of labour; here, he tells us that every (male) member of civil society ' is somebody ' through 'his competence' and his 'regular income and means of support', i.e. possesses the social status of a full-fledged citizen, and will find 'his honour' in this recognised existence as a professional (Hegel 1991 [1821], § 253).